67 Weight changes after treatment in a colombian breast cancer retrospective cohort. (18th September 2019) - Herrera Rueda, GA; Alvarado De la Hoz, CE; Amaya Marshall, AJ; Martinez Moreno, NA; Rodriguez, R; Romero Gamboa, DG; Lozano Jiménez, JF
Abstract : Objectives: The variability of weight during and after the treatment of breast cancer has been related to different disease outcomes. The objective of this study is to describe the weight variability in women with breast cancer and establish its relationship with the recurrence of disease in the 48 months following treatment. Methods: Descriptive retrospective cohort study with non-probabilistic convenience sampling of women with luminal A, stage IIIB invasive breast cancer, treated in two reference oncology centers in northeastern Colombia with surgery, chemotherapy, radiotherapy and hormone therapy during 2010 to 2017. An analysis of central tendency, univariate and bivariate measures was performed and comparisons of proportions with Chi-square (p<0.05) were assessed. Results: 1660 clinical records were reviewed, of which 74 patients met the inclusion criteria. At the start of the follow-up, 52 years was the mean age, and the average weight and BMI was 67kg and 26.9, respectively; none of the patients presented low weight, in fact, 68% of them were overweight. Also was noticed that no woman was classified as underweight at the end of the follow-up despite the treatment, actually increasing the number of patients in the overweight group (p<0.05). A possible relationship between the occurrence of metastasis and the weight variability subgroup was identified. Conclusions: This is the first study that analyzes the weight variability in women with breast cancer in Colombia. The results show a tendency to overweight in this population and its possible relationship to the occurrence of metastasis at the end of the follow-up.